2008
DOI: 10.1080/13550280701708427
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic correlates of hepatitis C virus in brain: A pilot study

Abstract: Hepatitis C virus (HCV) has been detected in the brain tissues of 10 individuals reported to date; it is unclear what clinical factors are associated with this, and with what frequency it occurs. Accordingly, a pilot analysis utilizing reverse transcriptase-polymerase chain reaction (RT-PCR) to detect and sequence HCV in premortem plasma and postmortem brain and liver from 20 human immunodeficiency virus (HIV)-infected and 10 HIV-naïve individuals was undertaken. RNA encoding the first 126 amino acids of the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 45 publications
0
41
0
1
Order By: Relevance
“…Negative-strand HCV RNA was found in autopsy brain tissue (34), and two independent groups of researchers reported that the brain-derived HCV variants were more closely related to the virus present in the lymphoid system than to the virus circulating in serum (10,34). Differences between HCV sequences in the brain and those circulating in plasma also were reported by others (8,28). Finally, a recent study by Letendre et al (23) demonstrated the presence of HCV proteins in brain tissue by Western blotting and immunostaining.…”
mentioning
confidence: 80%
“…Negative-strand HCV RNA was found in autopsy brain tissue (34), and two independent groups of researchers reported that the brain-derived HCV variants were more closely related to the virus present in the lymphoid system than to the virus circulating in serum (10,34). Differences between HCV sequences in the brain and those circulating in plasma also were reported by others (8,28). Finally, a recent study by Letendre et al (23) demonstrated the presence of HCV proteins in brain tissue by Western blotting and immunostaining.…”
mentioning
confidence: 80%
“…However, data on the association between the virus in the brain and impaired cognitive function are still lacking. Indeed, replication of quasispecies is very low within the brain; HCV RNA is almost undetectable in the cerebrospinal fluid [33,34] and there is no correlation between viral load and cognitive impairment in patients with HCV infection [20] . However, this is sometimes also the case for other HCV-related complications, such as cryoglobulinemia or vasculitis [35] .…”
Section: Inflammation and Hcvmentioning
confidence: 99%
“…10 000 (15 % aller HIV-Patienten), in den USA 240 000 (30 % aller HIV-Infizierten) mit HCV koinfiziert [73]. Die wenigsten dieser Patienten sind adäquat therapiert und es wird angenommen, dass eine HCV-Koinfektion mit einem beschleunigten Verlauf der HIV-Infektion bei unbehandelten Patienten assoziiert sein könnte [74]. Neurologische Symptome finden bei HCV-Patienten mehr und mehr Beachtung.…”
Section: Bedeutung Von Komorbiditätenunclassified